2015
DOI: 10.1002/ptr.5325
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Safety and Efficacy of Moringa oleifera

Abstract: Moringa oleifera leaves, seeds, bark, roots, sap, and flowers are widely used in traditional medicine, and the leaves and immature seed pods are used as food products in human nutrition. Leaf extracts exhibit the greatest antioxidant activity, and various safety studies in animals involving aqueous leaf extracts indicate a high degree of safety. No adverse effects were reported in association with human studies. Five human studies using powdered whole leaf preparations of M. oleifera have been published, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
247
0
17

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 400 publications
(302 citation statements)
references
References 66 publications
4
247
0
17
Order By: Relevance
“…In Rajasthan (a semi-arid region of India), parts of this plant form a common ingredient of many dishes cooked in a household kitchen (Bhargave et al 2015). Studies on humans and animals have revealed that the M. oleifera is quite safe for consumption (Stohs and Hartman 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Rajasthan (a semi-arid region of India), parts of this plant form a common ingredient of many dishes cooked in a household kitchen (Bhargave et al 2015). Studies on humans and animals have revealed that the M. oleifera is quite safe for consumption (Stohs and Hartman 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic potential and medicinal properties of M. oleifera are extensively reviewed [50,51]. Stohs and Hartman [52] described the physiological and pharmacological activities of the leaves, seeds, bark, roots, sap, and flowers of M. oleifera.…”
Section: Biological Activity and Therapeutic Potential Of M Oleiferamentioning
confidence: 99%
“…However, toxicity studies on the seed and root extracts were inconclusive. In general, based on human, animal and in vitro studies, it appears that various extracts of M. oleifera are safe when used at nutritional and normal doses equivalent to 4.6 to 8 gm of the leaf powder daily (37).…”
Section: Moringa Sppmentioning
confidence: 99%